2019
DOI: 10.1103/physrevmaterials.3.054005
|View full text |Cite
|
Sign up to set email alerts
|

Phase stability of two-dimensional monolayer As1xPx solid solutions revealed by a first-principles cluster expansion

Abstract: The phase stability of two-dimensional monolayer As 1−x P x solid solutions, exhibiting the puckered (α phase) and buckled (β phase) structures are investigated using a first-principles cluster-expansion method. Canonical Monte Carlo simulations, together with harmonic approximation, are performed to capture the influences of thermally induced configurational disorder and lattice vibrations on the phase stability of monolayer As 1−x P x. We first demonstrate that, as the temperature approaches 0 K, the monolay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Applications range from nanostructured electronics such as FET channels (1,2) to Li-and Na-ions batteries (3,4) and solid lubrication (5)(6)(7). While theoretical and experimental studies tend to focus on the electronic and mechanical properties, the phase behaviour of low dimensional materials, equally important to inform synthesis strategies and understand service life, remains an open question (8).…”
Section: Introductionmentioning
confidence: 99%
“…Applications range from nanostructured electronics such as FET channels (1,2) to Li-and Na-ions batteries (3,4) and solid lubrication (5)(6)(7). While theoretical and experimental studies tend to focus on the electronic and mechanical properties, the phase behaviour of low dimensional materials, equally important to inform synthesis strategies and understand service life, remains an open question (8).…”
Section: Introductionmentioning
confidence: 99%
“…The components of b-As x P 1– x can be optimized for specific uses with the alloying strategy. , Due to the tunability of their layer numbers and chemical composition environment, the band gap of bulk b-As x P 1– x can be fully turned over the range from 0.15 to 0.3 eV. Several recent theoretical studies on b-As x P 1– x have also revealed its excellent physicochemical properties. For example, Shojaei et al investigated the electrical structure in detail and estimated its carriers up to 10 000 cm 2 V –1 s –1 , and Sun et al calculated its lattice thermal conductivity, highlighting the effect of atomic arrangement . Zhu et al calculated the electronic band structures of As x P 1– x and expected a structure transition from α-phase to β-phase at x = 0.93. , Meanwhile, As x P 1– x has been used experimentally in photonics devices such as photodetectors, saturable absorbers, optical logic devices, etc. ,, The broadband nonlinear optical response of As 0.4 P 0.6 nanomaterial has high optical stability by virtue of spatial self phase modulation (SSPM) .…”
mentioning
confidence: 99%